Interactive Socio-Scientific Inquiry: The Effects on Creative Thinking Skills - Indriani, Tasya; Jayanti, Ummi Nur Afinni Dwi (FKIP Universitas Lampung, 2022)
Creative thinking skills are an important factor in learning whose implementation is still being questioned in various schools in Indonesia. This quantitative study aims to determine the effect of the Interactive Socio-Scientific Issue model on the creative thinking ability of students in class X SMA/MA. This study involved 60 students who were positioned as research subjects. Creative thinking skills data were collected using the essay test integrated creative thinking skills rubric. The data collected were analyzed using descriptive statistics in the form of mean and analytic statistics in the form of the ANCOVA test. The results of this study inform that the profile of creative thinking skills of class X high school students has increased which can be seen from the results of pre-test and post-test in the experimental class and control class. Furthermore, indicators in creative thinking skills that developed in this study were indicators of flexible thinking in the experimental class and the highest improvement in the original thinking aspect which was seen based on the results of the post-test that had been carried out. Following up on the findings of this study, empowering creative thinking skills using the Interactive Socio Scientific Issue model is appropriate for use in subjects, especially Biology Keywords: creative thinking, environmental change, socio-scientific issue. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp995-1005